Movements and survival of Lesser Snow Geese Chen caerulescens caerulescens wintering in two habitats along the Gulf Coast, Louisiana - Jónsson, Jón Einar; Frederiksen, Morten; Afton, Alan D. (Wildfowl, 2014)
Lesser Snow Geese Chen caerulescens caerulescens (hereafter Snow Geese) use two wintering habitats in southwest Louisiana. Snow Geese in coastal marshes generally have larger bodies and proportionally thicker bills, longer skulls and longer culmen lengths than do those in adjacent rice-prairies. An important question is whether or not these morphs are sub-populations that segregate during winter. Using a markresightings analysis of observations of neck-collared birds, annual apparent survival (Φ) and movement probabilities (Ψ) of Snow Geese were compared between habitats during winters 2001/02–2003/04. The analysis tested the hypothesis of Alisauskas (1998), based on his data collected in winter 1983/84, that larger bill size would increase Φ and decrease Ψ in coastal marshes. Specific predictions were that: 1) larger-billed Snow Geese would be relatively more likely to move from rice-prairies to coastal marshes, or have higher Φ within coastal marshes; and 2) smaller-billed Snow Geese would be relatively more likely to move from coastal marshes to rice-prairies, or have lower Φ within coastal marshes. Estimated annual Φ (± s.e.) was 0.601 ± 0.082, independent of both habitat and time interval. A body size covariate, used to index the morphs, did not improve model fit, indicating that Φ was unrelated to body size after accounting for habitat effects. Estimates of Ψ differed widely between intervals (November–December inclusive, versus the rest of the year) and habitats; they averaged 0.18 (range: 0.00–0.56) for birds moving from rice-prairies to coastal marshes and 0.57 (0.00–0.98) on moving from coastal marshes to rice-prairies. Movements of marked individuals were frequent from marshes to rice-prairies, and Ψ was independent of body size. However, movement probabilities were dependent on time intervals and we interpret such interval-specific movement probabilities as responses to shifts in environmental conditions. Thus, the two groups differ in morphology and generally remain segregated except that they mix during intervals of high movements, which occur every 1–3 years.